2016
DOI: 10.1097/md.0000000000002921
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepcidin Levels in Childhood-Onset Ischemic Stroke

Abstract: Recently, hepcidin, an antimicrobial-like peptide hormone, has evolved as the master regulator of iron homeostasis. Despite the growing evidence of iron imbalance in childhood-onset ischemic stroke, serum hepcidin level in those patients has not yet been researched.In this study, we aimed to estimate serum (hepcidin) level in acute ischemic stroke (AIS) patients and to investigate whether subcutaneous enoxaparin sodium, which is a low-molecular-weight heparin (LMWH) derivative, could modulate serum hepcidin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…We observed increases in ferritin levels in association with clinical events suggestive of the presence of fetal hypoxia-ischemia and acidosis, as well as birth asphyxia, represented by elevated lactate dehydrogenase levels, low blood pH and base excess, and low Apgar scores. These ndings are consistent with studies that reported marked elevation of serum ferritin levels after the onset of stroke [40][41][42] and with a preclinical study in rodents, which showed that temporary occlusion of the middle cerebral artery resulted in the upregulation of ferritin synthesis at both mRNA and protein levels [41] .…”
Section: Discussionsupporting
confidence: 91%
“…We observed increases in ferritin levels in association with clinical events suggestive of the presence of fetal hypoxia-ischemia and acidosis, as well as birth asphyxia, represented by elevated lactate dehydrogenase levels, low blood pH and base excess, and low Apgar scores. These ndings are consistent with studies that reported marked elevation of serum ferritin levels after the onset of stroke [40][41][42] and with a preclinical study in rodents, which showed that temporary occlusion of the middle cerebral artery resulted in the upregulation of ferritin synthesis at both mRNA and protein levels [41] .…”
Section: Discussionsupporting
confidence: 91%
“…S-1337; Peninsula Laboratories, Bachem, CA). This ELISA system was used in a number of previous studies [ 16 , 17 ]. If patients had additional cytopenia (white blood cell count < 4000/μL, platelet count < 10 × 10 4 /μL) and/or abnormal white blood cell differentiation, haematological abnormalities were suspected and we added a haematological examination, including bone marrow aspiration.…”
Section: Methodsmentioning
confidence: 99%
“…Significant hepatic hepcidin disturbance can cause brain iron-overload, as it has been observed in cirrhotic patients [ 39 ]. But, in acute conditions, such as acute ischemic stroke and intracerebral hemorrhage, serum hepcidin levels are increased and they contribute to iron-load in ischemic brain [ 111 114 ]. What is more, brain damage worsens during ischemia when accompanied with increased systemic hepcidin levels, due to increased brain oxidative injury [ 18 ].…”
Section: Hepcidin In Brain Diseasesmentioning
confidence: 99%